CAPACITIVE BASED CMOS-MEMS MICROACTUATOR FOR BIOMEDICAL APPLICATION - Samuri, Marfarahain (Universiti Teknologi PETRONAS, 2011)
The purpose of this project is to design electrostatic microacluator for biomedical application using CMOS and MEMS. The technology of microelectromechanical system (MEMS) is widely used in many daily applications such as aerospace Microsystems, biomedical applications, consumer electronic devices and so on. Specifically in biomedical applications, the experimentation always related to a macro meter objects manipulation. Due to that constraint, the tools that being used are also in macro meter-sized. Therefore, basically this project implements a micro actuator with an integrated capacitive force sensor which can be used in biomedical applications in handling cells and micron-size objects. An actuator for macro-size objects is already in market and it is not suitable to be used to the small cells like micron-cells. In my research, I had determined that there are several actuation principles of different types of gripper which are eleclmstatic, electromagnetic, electro thermal and electro osmotic. The problem where the procedure of handling the active cells must be taken seriously now can be solved with the invention of the grippers. Tn order to design the structure of this device, certain requirements should be taken into considerations. This project will improve the design for microactuator by applying electrostatic principles. The device then simulated in fvlATLAB to find other parameters needed for the microgripper. The performance of this device will be determined by its sensitivity for gripping the Hela cells. The device can be operated with 58V of actuator voltage supply and produced 9.9238 J.lN to have displacement of 1 J.lm. The results show that the device can be used with low voltage and able to be used for cell manipulations.